In-hospital time to treatment of patients with acute ST elevation myocardial infarction treated with primary angioplasty: determinants and outcome. Results from the registry of percutaneous coronary interventions in acute myocardial infarction of the Arbeitsgemeinschaft Leitender Kardiologischer Krankenhausärzte. Issue 8 (14th July 2005) - Zahn, R; Vogt, A; Zeymer, U; Gitt, A K; Seidl, K; Gottwik, M; Weber, M A; Niederer, W; Mödl, B; Engel, H-J; Tebbe, U; Senges, J
Abstract : Objective: To determine the predictors of time between presentation and primary angioplasty and the influence of this delay time on in-hospital mortality in clinical practice. Design: Analysis of data from the registry of percutaneous coronary interventions in acute myocardial infarction of the Arbeitsgemeinschaft Leitender Kardiologischer Krankenhausärzte (ALKK). Patients: Data of 4815 patients registered at 80 hospitals between 1994 and 2000 were analysed. Results: Mean age of the patients was 61.4 (12.5) years. Cardiogenic shock was present in 14.1%. Mean time from admission to primary angioplasty ("door to angiography" time) was 83 (122) minutes. Logistic regression analysis showed the presence of a bundle branch block (odds ratio (OR) 1.95, 95% confidence interval (CI) 1.15 to 3.29), prior coronary artery bypass grafting (OR 1.67, 95% CI 1.08 to 2.59), pre-hospital delay > 3 hours (OR 1.61, 95% CI 1.37 to 1.89), and female sex (OR 1.21, 95% CI 1.01 to 1.45) to be independently associated with longer door to angiography times, whereas a higher hospital volume of performing primary angioplasty (OR 0.53, 95% CI 0.46 to 0.62) and the year of the investigation (OR 0.96, 95% CI 0.92 to 1.00) were independently associated with shorter door to angiography times. Independent predictors of in-hospital mortality were cardiogenic shock (41.6% v 4.0% without cardiogenic shock, p < 0.0001), technical success (29.2% with TIMI (thrombolysis in myocardial infarction) flow < 3 v 6.5% with TIMI flow 3, p < 0.0001), age (16.5% ⩾ 70 years v 6.6% < 70, p < 0.0001), three vessel disease (16.5% v 6.8% with < 3 vessel disease, p < 0.0001), anterior location of infarction (12% v 7.4% without anterior infarction, p < 0.0001), year of inclusion (adjusted OR 0.92 per year, p = 0.011), and volume of primary angioplasty at the hospital (11% for < 20 angioplasty procedures/year v 8.3% for ⩾ 20/year, p = 0.027) but not the door to angiography time (adjusted OR 1.14 per tertile, p = 0.397). Conclusions: In current clinical practice in Germany median door to angiography time is quite short (83 (122) minutes). Some patients and hospital factors are independently associated with a longer door to angiography time. Within the observed short in-hospital delays door to angiography time did not influence in-hospital mortality. However, efforts to keep them as short as possible should be continued.